Evaluation of the Novel Method and the Regression Equation for Calculation of Low-Density Lipoprotein Cholesterol (Journal of Enam Medical College, 2015)
Background: Friedewalds formula (FF) is used worldwide to calculate low-density lipoprotein cholesterol (LDL-chol). But it has several shortcomings: overestimation at lower triglyceride (TG) concentrations and underestimation at higher concentrations. In FF, TG to very low-density lipoprotein cholesterol (VLDL-chol) ratio (TG/VLDL-chol) is considered as constant, but practically it is not a fixed value. Recently, by analyzing lipid profiles in a large population, continuously adjustable values of TG/VLDL-chol were used to derive a novel method (NM) for the calculation of LDL-chol. Objective: The aim of this study was to evaluate the performance of the novel method compared with direct measurement and regression equation (RE) developed for Bangladeshi population. Materials and Methods: In this cross-sectional comparative study we used lipid profiles of 955 adult Bangladeshi subjects. Total cholesterol (TC), TG, HDL-chol and LDL-chol were measured by direct methods using automation. LDL-chol was also calculated by NM and RE. LDL-chol calculated by NM and RE were compared with measured LDL-chol by twotailed paired t test, Pearsons correlation test, bias against measured LDL-chol by Bland-Altman test, accuracy within ±5% and ±12% of measured LDL-chol and by inter-rater agreements with measured LDL-chol at different cut-off values. Results: The mean values of LDL-chol were 110.7 ± 32.0 mg/dL for direct measurement, 111.9 ± 34.8 mg/dL for NM and 113.2 ± 31.7 mg/dL for RE. Mean values of calculated LDL-chol by both NM and RE differed from that of measured LDL-chol (p